Then we take Berlin - Lawton, John, 1949- (New York : Atlantic Monthly Press, 2013)
In 1963, freelance private investigator Joe Wilderness, a former MI6 agent and black market con artist, agrees to one last Berlin scam, which involves smuggling people, and brings his World War II gang of accomplices together once again.
PBK.
Keywords: Private investigators -- Fiction; Human smuggling -- Germany -- Berlin -- Fiction; Cold War -- Fiction; Berlin (Germany) -- Fiction; Suspense fiction